Dependency syndrome by communities or insufficient ingestion period by benefactor organizations? The Chirumanzu caritas community gardening project experiencein Zimbabwe - Matsa, Mark; Dzawanda, Beauty (American Research Institute for Policy Developmen, 2016)
http://jgesnet.com/journals/jges/Vol_2_No_1_June_2014/7.pdf